Bowel preparation before colonoscopy in the era of mass screening for colo-rectal cancer: A practical approach - Parente, F.; Marino, B.; Crosta, C. (Digestive and liver disease, 2009)
Colonoscopy constitutes the principal investigation for colo-rectal neoplasms due to its ability to detect and remove most of precancerous lesions; due to the ongoing or planned colon cancer screening programs in many European countries we should expect an enormous increase in colonoscopic demand over the next few years. Diagnostic accuracy and therapeutic safety of colonoscopy strictly depends upon the quality of bowel cleansing which is often perceived as the most unpleasant part of the procedure in individuals undergoing this examination. The ideal preparation for colonoscopy should reliably empty the colon from all faecal material allowing the optimal visualization of the entire colonic mucosa without causing great patient's discomfort nor significant shifts in fluids or electrolytes. Standard PEG solutions and sodium phoshate (NaP) compounds are the most frequently used preparations; both are accepted and relatively well tolerated by the majority of patients undergoing colonoscopy; however, NaP compounds should be avoided in elderly subjects as well as in those with congestive heart failure, renal and hepatic insufficiency or taking diuretics, ACE inhibitors or angiotensin receptor blockers, since they can induce severe electrolyte and/or fluid disturbances. Standard PEG solutions are often taken incompletely due to the low palatability and the high volume of liquids required which induce nausea and vomiting with negative consequences in terms of colon cleansing. Reduced volume and better palatability of PEG solutions, such as those obtained with the newest PEG formulations, as well as improved patient education concerning the importance of bowel cleansing could undoubtedly increase compliance with oral bowel preparations and promote adherence to colo-rectal cancer screening programs.